2023
DOI: 10.1002/zamm.202200622
|View full text |Cite
|
Sign up to set email alerts
|

Numerical heat featuring in Blasius/Sakiadis flow of advanced nanofluid under dissipation and convective heat condition effects

Adnan,
Nidhish Kumar Mishra,
Ishtiaque Mahmood
et al.

Abstract: The study of advanced nanofluids termed as Tetra nanofluid is of potential interest now a days. These fluids are upgraded generation of conventional nano to ternary hybrid nanofluids with outstanding characteristics. Applications of this class frequently occur in applied thermal engineering, nano‐lubrication, chemo‐therapy, chemical engineering, oil paint industry, coolant of nuclear plant and many other applied research areas. This study concerns with the development of innovative thermophysical rules for Tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 53 publications
0
0
0
Order By: Relevance
“…Some advanced research topics covering the flow of nanofluid can be found in ref. [16][17][18][19][20][21][22][23][24]. Many scientists, especially in the last few decades, have become interested in the study of the flow via porous channels primarily because of the technology's widespread use in biological, industrial, and engineering fields.…”
Section: Introductionmentioning
confidence: 99%
“…Some advanced research topics covering the flow of nanofluid can be found in ref. [16][17][18][19][20][21][22][23][24]. Many scientists, especially in the last few decades, have become interested in the study of the flow via porous channels primarily because of the technology's widespread use in biological, industrial, and engineering fields.…”
Section: Introductionmentioning
confidence: 99%